INCIDENCE AND LOW TEMPRATURE SURVIVAL OF COAGULASE POSITIVE STAPHYLOCOCCI IN FISHERY PRODUCTS - IYER, T. S GOPALAKRISHNA; SHRIVASTAVA, K P (Fishery Technology, 2017)
Coagulase-positive staphylococci was found to be absent in all the frozen samples of lobsters, cuttle fish, cat fish, seer fish and red snapper examined. Coagulasepositive staphylococci were present in 38 % of the cooked frozen shrimps and only 16 of the samples had staphylococci count more than 100/g. In the case of headless, peeled and deveined, peeled undeveined shrimps, the incidence of the organism was 6, 12 and 16 %, respectively. The study indicated that the incidence of coagulase-positive staphylococci is not a serious problem in frozen fishery products processed in this country. There was remarkable difference in the rate of destruction of coagulasepositive staphylococci in raw and cooked shrimps during freezing and frozen storage.